THE IMPACT OF SHIRORO DAM PROJECT ON PRODUCTIVITY AND LIVELIHOOD DIVERSIFICATION OF RURAL FISHERFOLKS IN NIGER STATE, NIGERIA - Yusuf Usman Oladimeji; AY B Abubakar; Zakari Abdulsalam (Agricultural Socio-Economics Journal, 2020)
The interdependence of water, food and energy are widely recognized as important drivers of socioeconomic development. The objective of the study was to assess the impact of Shiroro Dam Project (SDP) on productivity and livelihood diversification of rural fisherfolks in Niger state, Nigeria. Primary data were collected from the fisherfolks with the aid of structured questionnaires. A multistage sampling procedure was used to select 363 fisherfolks from two LGAs, twelve villages and 1,210 sample frames. Two hundred and sixty (267) fisherfolks who are non-beneficiaries of SDP were also selected as counterfactual to examine the impact. The data were analyzed using descriptive statistics, Tobit regression, Propensity Score Matching (PSM) and the Local Average Treatment Effect (LATE) models. Result revealed that fishery activities were the most important source of income (68.3%) among the fisherfolks. The coefficients of length of fishing gears (-0.400), capacity of outboard engine (-0.005), household size (0.008), credit accessed for fishery (0.052) and per capita expenditure (0.306) were statistically significant factors influencing the extent of livelihood diversification of Shiroro dam fisherfolks. There was statistically significant difference between the mean income of fisherfolks (₦56,119.06 per annum) who benefitted from SDP and counterfactual (₦37,876.80). Similarly, the results of impact of SDP on productivity of fisherfolks revealed that the treatment effect on the treated (ATT) increases productivity of the benefitted fisherfolks by 2.8273 (38.1%), that ATU had a significant and positive impact (0.1282) on productivity, and the average effect of the treatment (ATE) for SDP fisherfolks has a positive difference of 0.6654 compared to the treated category. Fisherfolks should form a formidable social organization to benefit from economy of bulk purchase of farm inputs especially fishing gears and outboard engine, farm advisory services, increased access to credit, and access to other modern fishing techniques.